Bacterial extracellular vesicles affect endocrine therapy in MCF7 cells. Issue 18 (7th May 2021) - An, Jeongshin; Kim, Jong Bin; Yang, Eun Yeol; Kim, Hye Ok; Lee, Won-Hee; Yang, Jinho; Kwon, Hyungju; Paik, Nam Sun; Lim, Woosung; Kim, Yoon-Keun; Moon, Byung-In
Abstract: Background: : The microbiome is important in the development and progression of breast cancer. This study investigated the effects of microbiome derived from Klebsiella on endocrine therapy of breast cancer using MCF7 cells. The bacterial extracellular vesicles (EVs) that affect endocrine therapy were established through experiments focused on tamoxifen efficacy. Methods: : The microbiomes of breast cancer patients and healthy controls were analyzed using next-generation sequencing. Among microbiome, Klebsiella was selected as the experimental material for the effect on endocrine therapy in MCF7 cells. MCF7 cells were incubated with tamoxifen in the absence/presence of bacterial EVs derived from Klebsiella pneumoniae and analyzed by quantitative real-time polymerase chain reaction and Western blot. Results: : Microbiome derived from Klebsiella is abundant in breast cancer patients especially luminal A subtype compared to healthy controls. The addition of EVs derived from K pneumoniae enhances the anti-hormonal effects of tamoxifen in MCF7 cells. The increased efficacy of tamoxifen is mediated via Cyclin E2 and p -ERK. Conclusion: : Based on experiments, the EVs derived from K pneumoniae are important in hormone therapy on MCF7 cells. This result provides new insight into breast cancer mechanisms and hormone therapy using Klebsiella found in the microbiome.